Comparative Profitability of Onions Harvested as Green and Dry (Mature) in Botswana - Baliyan, SP; Baliyan, PS (International Journal of Agricultural Research, Innovation and Technology, 2013)
This study was an attempt to calculate and compare the profitability of onions harvested as green and dry (mature) in Botswana. Half of the planted onions were harvested and sold as green and half were harvested and sold as dry onions. The cost of production of green onions was 32.78% higher than the cost of production of dry onions. The irrigation and marketing expenses contributed the highest difference in the cost of production of green and dry onions. The major cost item contributing to the cost of green onions production was marketing cost (32.86%) followed by irrigation cost (23.77%) and harvesting cost (18.53%) whereas the highest cost of production for dry onions was contributed by irrigation (38.58%) followed by marketing (19.45%) and planting (11.96%). The marketing cost for green onions was almost double (35.6%) as compare to the dry onions (18.2%). The total return from green onions was 50.90% higher than the returns from dry onions. Gross margin of onions harvested as green was 63% higher than the gross margin from dry onions, which indicated that the production of green onions is more profitable as compare to production of dry onions. The farmers preferred onion harvested as green because it generates regular and higher returns than onions harvested as mature. Government should support farmers through some policies such as Minimum Support Price (MSP) for dry onions, distribution of Mini FertiSeed Kit (Seeds of improved varieties and fertilizer package), construction of storages and formation of cooperatives. Int. J. Agril. Res. Innov. & Tech. 3 (1): 73-77, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16096